Neural Correlates of Selective Attention With Hearing Aid Use Followed by ReadMyQuips Auditory Training Program. Issue 1 (January 2017) - Rao, Aparna; Rishiq, Dania; Yu, Luodi; Zhang, Yang; Abrams, Harvey
Abstract : Objectives: The objectives of this study were to investigate the effects of hearing aid use and the effectiveness of ReadMyQuips (RMQ), an auditory training program, on speech perception performance and auditory selective attention using electrophysiological measures. RMQ is an audiovisual training program designed to improve speech perception in everyday noisy listening environments. Design: Participants were adults with mild to moderate hearing loss who were first-time hearing aid users. After 4 weeks of hearing aid use, the experimental group completed RMQ training in 4 weeks, and the control group received listening practice on audiobooks during the same period. Cortical late event-related potentials (ERPs) and the Hearing in Noise Test (HINT) were administered at prefitting, pretraining, and post-training to assess effects of hearing aid use and RMQ training. An oddball paradigm allowed tracking of changes in P3a and P3b ERPs to distractors and targets, respectively. Behavioral measures were also obtained while ERPs were recorded from participants. Results: After 4 weeks of hearing aid use but before auditory training, HINT results did not show a statistically significant change, but there was a significant P3a reduction. This reduction in P3a was correlated with improvement in d prime ( d ′) in the selective attention task. Increased P3b amplitudes were also correlated with improvement in d ′ in the selective attention task. After training, this correlation between P3b and d ′ remained in the experimental group, but not in the control group. Similarly, HINT testing showed improved speech perception post training only in the experimental group. The criterion calculated in the auditory selective attention task showed a reduction only in the experimental group after training. ERP measures in the auditory selective attention task did not show any changes related to training. Conclusions: Hearing aid use was associated with a decrement in involuntary attention switch to distractors in the auditory selective attention task. RMQ training led to gains in speech perception in noise and improved listener confidence in the auditory selective attention task.